Cardio-Protective Effect of Malvidin against Doxorubicin-Stimulated Cardiotoxicity in Experimental Rat Models - Mi, Xiaolong; Ren, Lili Zhang Yunxia; Li, Tong; Cheng, Jinfang (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Malvidin (MAL) is an anthocyanidin having therapeutic characteristics that provide several therapeutic advantages. Doxorubicin (DOX) is a valuable anti-tumor drug with a wider anticancer range; nevertheless, DOX's cardiotoxic side effects via oxidative stress and apoptosis restrict its clinical use. There are various old and modern solutions that can aid with this predicament. Even decades after the drug's side effects were revealed, no successful strategy for managing this clinical disease has been found. The goal of the present investigation is to study the cardioprotective ability of the natural compound MAL against DOX-stimulated cardiotoxicity in rat models. Materials and Methods: Upon induction of cardiotoxicity and administration of MAL, assessment of parameters including heart and body weight, antioxidant levels, serum lipid profile, cardiac biomarker levels and inflammatory marker levels were carried out. Results: It was discovered that treatment with MAL remarkably protected the mice from DOX-triggered cardiotoxicity, as evidenced by increased heart and body weight, antioxidant enzyme levels, reduced levels of cardiac biomarker levels and inflammatory parameters and improved heart morphology. Conclusion: Thus, MAL demonstrated to be a valuable substance for protection of cardiac tissues against DOX-stimulated cardiotoxicity.
Keywords: Anti-inflammatory; Cardiotoxicity; Doxorubicin; Malvidin; Oxidative stress